Astrology and the Demotic Press: Almanacs in Eighteenth-Century England - DRAGOŞ, Ivana (Anafora, 2023)
The present article focuses on the eighteenth-century English almanac as an iconic element of the demotic press, on the one hand, and as a literary commodity published by the Stationers’ Company, a guild of artisans involved in the printing trade. Engaged in popularising their astrological content as scientific observations, almanacs were classified by the elite as low reading in tune with the Company’s supply and demand policy. My task is to apply the “high” / “low” culture dichotomy to English almanacs and to examine the way in which they marked a radical change from an archaic, superstitious, and irrational frame of mind to a rational, scientific, and, implicitly, modern worldview backed by the Scientific Revolution. Last but not least, the paper will show that eighteenth-century English almanacs were sensitive to historical, national identity and popular patriotism issues and adhered to divergent religious and political allegiances exposed to the shafts of satire – the prevailing genre of the time – practiced by elite writers like Jonathan Swift or by famous almanac-compilers, such as George Parker and John Partridge.